2010
DOI: 10.4314/njps.v24i2.52901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alligator pepper (Zingiberaceae <i>Aframomum melegueta</i>) on first trimester pregnancy in Sprague Dawley Rats

Abstract: Summary: Alligator pepper (Aframomum melegueta) is a spice that is widely used in many cultures for entertainment, religious rites, food flavor and as a part of many traditional doctors medications. Pregnant women are among those who ingest Alligator pepper in these activities. This experiment was carried out to determine the health risk or benefit of Alligator pepper to pregnant women if any. Fifteen male rats and fifteen female rats of proven fertility from a pilot study were randomly paired in fifteen cages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Lawal et al [39] reported the hypotensive and antihypertensive effects in both normotensive and hypertensive human subjects and suggested that these may be due to central effect linked to peripheral vasodilatation. Gestational weight gain which is the major causes of pre-eclampsia (elevated blood pressure during pregnancy) was reported to have been reduced by aqueous extract of Alligator pepper [32]. However, Alligator pepper is not usually considered to be important from the nutritional point of view, even though it is widely used as spice in food and folkloric medicine throughout the world for health benefits.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lawal et al [39] reported the hypotensive and antihypertensive effects in both normotensive and hypertensive human subjects and suggested that these may be due to central effect linked to peripheral vasodilatation. Gestational weight gain which is the major causes of pre-eclampsia (elevated blood pressure during pregnancy) was reported to have been reduced by aqueous extract of Alligator pepper [32]. However, Alligator pepper is not usually considered to be important from the nutritional point of view, even though it is widely used as spice in food and folkloric medicine throughout the world for health benefits.…”
Section: Introductionmentioning
confidence: 98%
“…It is a tropical plant of genus Aframomum and belongs to the family Zingiberaceae (ginger family) of the angiosperms in the Kingdom plantae [31]. It is a spicy edible fruit that is cultivated in the tropics and often served along with kolanuts and alcoholic drinks to entertain guests [32]. Alligator pepper is popularly used as herbal remedy against a wide range of ailments in folkloric medicine in different parts of the world [31].…”
Section: Introductionmentioning
confidence: 99%
“…Au Bénin et au Nigéria, elle est utilisée comme ingrédient culinaire et rituels (Inegbenebor et al, 2009) (Ilic et al, 2010).…”
Section: Introductionunclassified
“…In a previous study, it was found that oral ingestion of high doses of granulated seeds of alligator pepper (333 mg/Kg body weight) caused termination of first trimester pregnancies in Sprague-Dawley rats [19], while intraperitoneal injection of low dose of the aqueous extract of the seeds of alligator pepper on the 4th day of gestation caused attenuation of gestational weight gain in mother rats and a reduction in litter weight of their litters without adverse effects on either mother rats or their litters [3]. These rat chow used in the previous study was grower's mash, which was also used in feeding the rats in the control group A in this study.…”
Section: Discussionmentioning
confidence: 99%